History of Micrornas: From Gene Controlling Development of Nematodes to a Promising Tool for Molecular Therapy - Dusan Brany (Acta Medica Martiniana)
MicroRNAs are short, single-stranded RNA molecules that typically consist of a 22-nucleotide sequence. Despite their small size, these molecules play an essential role in every type of human cell – regulation of gene expression on post-transcriptional level. Without this regulation, physiological functioning of cells, and thus also of complex organisms, would not be possible. Although microRNAs are extremely important, the mechanism of their function was explored and described relatively recently, in 1993, in Caenorhabditis elegans, a nematode approximately 1 millimeter in length. However, it took another seven years for miRNAs to be found and characterized in higher organisms, including humans. This discovery has increased scientific interest that continues nowadays, particularly due to the recognition that modulation of miRNA activity holds great promise as a therapeutic approach.